Musdus and Musdes as Innovative Models for Participatory Village Planning - Suroso, Agus (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2026)
The problem with village development generally lies in the low level of community participation in planning, resulting in decisions that tend to be elitist and do not reflect the community's real needs. This study aims to examine participatory planning practices through Hamlet Consultative Meetings (Musdus) and Village Consultative Meetings (Musdes) in Pejengkolan Village, Kebumen Regency, as well as the village government's strategies to increase participation and strengthen development governance. The research used a descriptive qualitative approach with observation, in-depth interviews, and documentation analysis techniques. The results show that Musdus and Musdes function as deliberative spaces allowing community aspirations to be gathered, discussed openly, and formalized into official documents, strengthening transparency and social legitimacy. The village government also implemented strategies to increase the capacity of officials, strengthen communication forums, and utilize data-based information systems to support objective and accountable decision-making. The integration of deliberation and information technology was able to strengthen local democracy, expand the space for participation, and realize inclusive, adaptive, and responsive village development governance to the socio-cultural needs of the community